Pengaruh Penilaian Kinerja Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Moderasi - Indria Hangga Rani; Mega Mayasari (Politeknik Negeri Batam, 2015)
Employees are very important factors in an organization to achieve organizational goals. The satisfactory performance of the employee is not created in an instant but it takes a continuous evaluation. This study aims to determine the effect of performance appraisal and employee performance and motivation influence on the relationship between performance appraisal and employee performance. This study uses simple regression analysis and test interaction or Moderated Regression Analysis (MRA). The population in this study includes permanent employees of Batam manufacturing company in Electronics Industry. Total Samples in this research Was 146 employee were selected using purposive sampling method. The data was collected using questionnaires. The results of the study showed that the assessment of performance brings a significant and positive effect on employee performance. This indicates that employees given assessment performance by his superior make the employee performance the higher. The other results state that the motivation variable is not moderating variable in the relationship between performance appraisal and employee performance.